Fatwa of the Wahdah Islamiyah Sharia Council regarding Guidelines for Friday Prayers during the Covid-19 Pandemic: An Academic Ijtihad Perspective - Muhlisah, Siti Nurul; Yusdani, Yusdani (Unisia, 2023)
The Covid-19 pandemic disrupted religious practices worldwide, posing significant challenges to maintaining communal worship while adhering to public health mandates. This study examines the fatwa issued by Wahdah Islamiyah, an Indonesian Islamic organization, which permitted the replacement of Friday prayers with Zuhr prayers at home during the pandemic. The fatwa demonstrates the adaptability of Islamic jurisprudence, leveraging progressive ijtihad to address unprecedented challenges. The study aims to explore the theological, jurisprudential, and methodological underpinnings of the fatwa, highlighting its alignment with maqasid shari’ah (objectives of Islamic law) and its implications for contemporary Islamic thought.  Using a qualitative approach, the research analyzes primary and secondary sources, including Quranic verses, Prophetic traditions, fiqh principles, and public health data. A multidimensional framework was employed to assess the integration of theological reasoning with interdisciplinary insights.  The findings reveal that Wahdah Islamiyah’s fatwa successfully balances religious obligations with public welfare by prioritizing harm prevention and public health. Grounded in classical jurisprudence, the fatwa reflects a dynamic application of Islamic law that incorporates sociological and scientific perspectives. It highlights the potential of smaller Islamic organizations to contribute to adaptive jurisprudence and demonstrates the relevance of progressive ijtihad in addressing global crises.  This study contributes to the discourse on contemporary Islamic jurisprudence, offering a model for integrating traditional principles with modern realities. It underscores the need for interdisciplinary collaboration in crafting legal frameworks that respond to evolving societal challenges while preserving the integrity of Islamic law.